When natural antibodies become pathogenic: autoantibodies targeted against G protein-coupled receptors in the pathogenesis of systemic sclerosis - Akbarzadeh, Reza; Müller, Antje; Humrich, Jens Y.; Riemekasten, Gabriela (Frontiers in Immunology, 2023)
Systemic sclerosis (SSc) is a chronic, multisystem connective tissue autoimmune disease with the highest case-specific mortality and complications among rheumatic diseases. It is characterized by complex and variable features such as autoimmunity and inflammation, vasculopathy, and fibrosis, which pose challenges in understanding the pathogenesis of the disease. Among the large variety of autoantibodies (Abs) present in the sera of patients suffering from SSc, functionally active Abs against G protein-coupled receptors (GPCRs), the most abundant integral membrane proteins, have drawn much attention over the last decades. These Abs play an essential role in regulating the immune system, and their functions are dysregulated in diverse pathological conditions. Emerging evidence indicates that functional Abs targeting GPCRs, such as angiotensin II type 1 receptor (AT1R) and the endothelin-1 type A receptor (ETAR), are altered in SSc. These Abs are part of a network of several other GPCR Abs, such as those directed to the chemokine receptors or coagulative thrombin receptors. In this review, we summarize the effects of Abs against GPCRs in SSc pathologies. Extending the knowledge on pathophysiological roles of Abs against GPCRs could provide insights into a better understanding of GPCR contribution to SSc pathogenesis and therefore help in developing potential therapeutic strategies that intervene with pathological functions of these receptors.